Handbook of positive psychology in schools [ - Gilman, Rich , 1968-; Huebner, Eugene Scott , 1953- (Routledge, 2009)
National surveys reveal that an inordinate number of students report high levels of boredom, anger, and stress in school, which often leads to their disengagement from learning and social development.